Effects of hydroxychloroquine plus favipiravir treatment on the clinical course and biomarkers in hospitalized covid-19 patients with pneumonia - KASAPOĞLU, UMUT SABRİ (My University, 2022)
SUMMARY – Background: The novel coronavirus disease 2019 (COVID-19) has a broad spectrum of clinical manifestations, the most common serious clinical manifestation of the coronavirus infection being pneumonia. Unfortunately, the optimal treatment approach is still uncertain. However, many studies have been conducted on the effectiveness of several medications in the treatment of COVID-19 infection. The aim of this study was to evaluate the effectiveness of the hydroxychloroquine (HCQ) + favipiravir (FAV) treatment regimen and HCQ alone by comparing the patient’s clinical response and laboratory results on the fifth day of treatment in patients hospitalized due to COVID-19 infection. Patients and methods: This retrospective cohort study was conducted in Malatya Training and Research Hospital between March 2020 and July 2020. The study included 69 patients with confirmed COVID-19 with pneumonia. The patients were divided into 2 groups, those receiving HCQ alone and those receiving the HCQ + FAV combination. Results: A total of 69 patients were included in the study, and the mean age was 60.09±15.56 years. A statistically significant decrease was observed in C-reactive protein (CRP) levels, at the end of the fifth day, in patients who received HCQ + FAV treatment (p=0.002), whereas there was no decrease in CRP levels in patients who received HCQ treatment alone. In addition, an increase in lymphocyte count and a better fever response was observed at the end of the fifth day in patients who received HCQ + FAV (p=0.008). However, there was no statistical difference between both treatment regimens in terms of hospital stay and treatment results (p=0.008, p=0.744, p=0.517). Conclusion: Although the combination of HCQ + FAV treatment was observed to be effective on CRP levels and fever response in patients with COVID-19 pneumonia, there was no difference in terms of hospital stay and discharge.
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; İç Hastalıkları; Yoğun Bakım; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Internal Diseases; Intensive Care; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SOLUNUM SİSTEMİ; YOĞUN BAKIM; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; RESPIRATORY SYSTEM; CRITICAL CARE MEDICINE; MEDICINE, GENERAL & INTERNAL; Solunum Bakımı; Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Akciğer ve Solunum Tıbbı; Dahiliye; Aile Sağlığı; Yoğun Bakım Tıbbı; Tıp (çeşitli); Genel Tıp; Respiratory Care; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Pulmonary and Respiratory Medicine; Internal Medicine; Family Practice; Critical Care and Intensive Care Medicine; Medicine (miscellaneous); General Medicine; Favipiravir; hydroxychloroquine; COVID-19; SARS-COV-2; pneumonia